2005
DOI: 10.1088/0953-4075/38/2/028
|View full text |Cite
|
Sign up to set email alerts
|

The electronically excited states of helium clusters: an unusual example for the presence of Rydberg states in condensed matter

Abstract: The nature of the electronically excited states of He clusters and their relaxation mechanisms are investigated by spectroscopy using monochromatized synchrotron radiation. Time correlated fluorescence excitation and energy resolved luminescence spectra of the clusters are recorded in separate wavelength ranges. The size of the clusters and the isotopic constitution is also varied. The spectral features are analysed and discussed particularly with regard to the high lying states and their possible Rydberg natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(74 citation statements)
references
References 33 publications
2
71
1
Order By: Relevance
“…The lack of intensity of high-lying excitations located in the bulk volume is consistent with the spectral features recorded using a solar-blind photomultiplier, as reported earlier. 8 The solar-blind multiplier is sensitive to fluorescence originating from the bulk-volume region and the spectrum reported shows many similarities with the short-lived fluorescence excitation spectrum, the features above 23 eV being even weaker. We interpret this result such that in bulk liquid helium The Journal of Physical Chemistry A ARTICLE Rydberg states higher than n = 2 are destabilized due to the Pauli repulsion and the low polarizability of bulk liquid helium.…”
Section: The Journal Ofmentioning
confidence: 88%
See 2 more Smart Citations
“…The lack of intensity of high-lying excitations located in the bulk volume is consistent with the spectral features recorded using a solar-blind photomultiplier, as reported earlier. 8 The solar-blind multiplier is sensitive to fluorescence originating from the bulk-volume region and the spectrum reported shows many similarities with the short-lived fluorescence excitation spectrum, the features above 23 eV being even weaker. We interpret this result such that in bulk liquid helium The Journal of Physical Chemistry A ARTICLE Rydberg states higher than n = 2 are destabilized due to the Pauli repulsion and the low polarizability of bulk liquid helium.…”
Section: The Journal Ofmentioning
confidence: 88%
“…3,5,8 Therefore, here we will only explain the most important features relevant to this paper. 3 He and 4 He clusters and droplets were produced using supersonic expansion of helium gas through an orifice of 5 μ in diameter (Frey GmbH, Berlin) into the vacuum.…”
Section: ' Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The blue-shift of 0.4 eV in the droplet is attributed to the repulsive interaction of the He Rydberg electron in the excited 2p 1 P 1 state with the droplet environment and can be thought of as the excess energy needed to form a Rydberg bubble state, in which the excitation is localized on a single atom, within the droplet. 36,37,62 In pure He droplets, the excited He* atom can be ejected from the droplet and fluoresce; this is how the electronic spectrum of pure He droplets was first measured. 36 In doped He droplets, this excitation can also migrate to the dopant atom and ionize it via Penning ionization within the droplet, that is, He*(2p 1 …”
Section: A Origins Of Features a And B: Penning Ionizationmentioning
confidence: 99%
“…This energy coincides with the lowest optically allowed electronic excitation in pure He droplets, as first observed by Joppien et al 36 via fluorescence excitation; this transition was assigned to the droplet analogue of the 2p 1 P 1 -1s 1 S 0 transition in the atomic He at 21.2 eV, blue-shifted and broadened in the droplet owing to collective interactions in the excited state. 37 The photoionization experiments showed that the SF 6 dopant was ionized via an indirect mechanism in which the He droplet was electronically excited and excitation transfer from the surrounding droplet ionized the dopant, that is, an intracluster Penning ionization mechanism. A similarly enhanced ion yield at 21.6 eV was seen by Kim et al 26 and Peterka et al 38 in photoionization experiments on He droplets doped with rare gas atoms (Rg) and SF 6 , respectively.…”
Section: Introductionmentioning
confidence: 99%